Ingeniería de yacimientos geotérmicos, pruebas de presión - Samaniego Verduzco, Fernando; Arellano Gómez, Víctor; Contreras, Enrique (My University, 1984)
A method of designing and analyzing pressure transient well tests of two-phase (steam-water) reservoirs Is given. Wellbore storage is taken into a ccount, and the duration of it is estimated. It is shown that the wellbore flow can dominate the downhale pressure signal completely such that large changes in the downhole pressure that might be expected because of changes in kinematic mobility are not seen. Changes in the flowing enthalpy from the reservoir can interact with the wellbore flow so that a temporary plateau in the downhole transient curve is measured. Application of graphical and nongraphical methods to determine reservoir parameters from drawdown tests is demonstrated.
Keywords: presión; discontinuity; two-dimensional; capabilities; subroutines